Key barriers and decision supports in revitalizing heritage buildings from investors' perspective in China: A case study in Guangzhou, China. - Kailun Fang; Yifei Wu (PLoS ONE)
In the decision-making process for investing in heritage buildings (HBs), various factors such as costs, interests, and tenancy terms influence investors decisions. Understanding the motivations of these investors can facilitate the involvement of social forces with diverse interests in adaptive reuse projects. This paper examines the primary barriers to revitalizing heritage buildings through adaptive reuse decision-making. The specific objectives of this study are as follows: i) To explore the barriers faced by investors in the adaptive reuse of heritage buildings. ii) To provide a comprehensive review of the factors influencing the adaptive reuse of heritage buildings, with a particular focus on developing countries. Through structured interviews with 19 investors and field research, three typical categories in the adaptive reuse decision-making process were identified: i) tenancy terms, ii) function, and iii) fire control problems. These findings indicate that vacancy is detrimental to the protection of heritage buildings, while rent plays a significant role in safeguarding them, as revealed by a correlation analysis using quantitative methods. Policymakers should better understand the expectations and needs of the public investors better to enhance support for optimal adaptive reuse decisions.